Penerapan Passive Leg Raising Terhadap Tekanan Darah Pada Pasien Post Operasi Coronary Artery Bypass Graft - Indra Wijaya (Jurnal Kesehatan Bhakti Husada, 2025)
Background: Coronary Artery Disease (CAD) is one of the cardiovascular diseases that is one of the biggest causes of death in Indonesia. Cardiovascular disease, including CAD, remains the leading cause of death in the world. In 2017, an estimated 17.9 million deaths (31% of all deaths) were caused by cardiovascular disease. The latest projections show that the number of deaths from cardiovascular disease, including CAD, will increase to reach 23.3 million deaths in 2030. Objective: To determine the application of Passive Leg Raising therapy to blood pressure in patients with Post Coronary Artery Bypass Graft surgery in the ICCU Room of Dr. Kariadi General Hospital, Semarang. Method: The method used is descriptive with a case study approach, which describes the nursing process by applying the application of Passive Leg Raising to blood pressure in patients with post coronary artery bypass graft surgery in the ICCU Room of Dr. Kariadi General Hospital, Semarang. Samples taken from two adult patients with a diagnosis of Coronary artery, performed with a semi-fowler position of 30°-45°. Results: The average systolic blood pressure of the case study subjects in the first application examination was 120 mmHg, in the second application examination 120 mmHg, and in the third application examination 127 mmHg. The average diastolic blood pressure in the first application examination was 80 mmHg, in the second application examination 80 mmHg, and in the third application examination 86 mmHg. The average MAP in the first application examination was 93 mmHg, in the second application examination 93 mmHg, and in the third application examination 99 mmHg. Conclusion: The intervention of Passive Leg Raising can increase blood pressure in post-coronary artery surgery patients and can be applied independently as a non-pharmacological management. Recommendation: The application of Passive Leg Raising can be used as a standard operating procedure (SOP) in coronary artery patients. Keywords: Post Coronary Artery Operation By Pass, Passive Leg Raising, Blood Pressure